Influence of pre-exercise acidosis and alkalosis on the kinetics of acid-base recovery following intense exercise - Robergs, R. A.; Hutchinson, K.; Hendee, S.; Madden, S.; Siegler, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2005)
The purpose of this study was to measure the recovery kinetics of pH and lactate for the conditions of pre-exercise acidosis, alkalosis, and placebo states. Twelve trained male cyclists completed 3 exercise trials (110% workload at VO2max), ingesting either 0.3 g/kg of NH4Cl (ACD), 0.2 g/kg of Na+HCO3- and 0.2 g/kg of sodium citrate (ALK), or a placebo (calcium carbonate) (PLAC). Blood samples (heated dorsal hand vein) were drawn before, during, and after exercise. Exercise-induced acidosis was more severe in the ACD and PLAC trials (7.15 ± 0.06, 7.21 ± 0.07, 7.16 ± 0.06, P < 0.05, for ACD, ALK, PLAC, respectively). Recovery kinetics for blood pH and lactate, as assessed by the monoexponential slope constant, were not different between trials (0.057 ± 0.01, 0.050 ± 0.01, 0.080 ± 0.02, for ACD, ALK, PLAC, respectively). Complete recovery of blood pH from metabolic acidosis can take longer than 45 min. Such a recovery profile is nonlinear, with 50% recovery occurring in approximately 12 min. Complete recovery of blood lactate can take longer than 60 min, with 50% recovery occurring in approximately 30 min. Induced alkalosis decreases metabolic acidosis and improves pH recovery compared to acidodic and placebo conditions. Although blood pH and lactate are highly correlated during recovery from acidosis, they recover at significantly different rates.